The Coronation of Bolesław Chrobry - Polak, Wojciech (A thousand years of Poland's presence among the elite of European states, 2026)
This study is devoted to the origins of the Polish state and the reign of Bolesław the Brave (992–1025). Particular emphasis is placed on those aspects of the first Polish king's rule that were directed toward securing the royal crown. The article examines the various spheres of Bolesław's activity: his efforts to strengthen and unify the state; his support for Christianization missions (those of St. Adalbert, St. Bruno of Querfurt, and the Five Martyr Brothers); his backing of Emperor Otto III's plans to establish a universal monarchy in which Bolesław would serve as king of the Slavic peoples; his territorial conquests; his decades-long war with Germany, concluded by the Peace of Bautzen in 1018; and his campaign against Kievan Rus in 1018. The article highlights that Bolesław the Brave was a ruler who strongly asserted his national pride while simultaneously embodying the virtues of a Christian knight. The concluding section provides a detailed discussion of the various aspects of Bolesław's royal coronation in 1025.